Vermiremediation of soils contaminated with mixture of petroleum products using Eisenia fetida - Njoku, Kelechi L.; Akinola, Modupe O.; Anigbogu, Catherine C. (Journal of Applied Sciences and Environmental Management, 2016)
In this paper, vermiremediation, a biological technique was utilized in order to clean-up soil contaminated with gasoline, diesel and spent engine oil using an earthworm - Eisenia fetida. The contaminated soils were analyzed for the total petroleum hydrocarbon (TPH) level every 24 hours over a period of 120 hours using gas chromatography. It was observed that at each sampling time, the soils samples without the earthworm had more quantity of TPH than the corresponding samples with the earthworms. Pentadecane, 2,6,10, trimethyl had 100% reduction after 120 hours followed by octadecane with 67.30 % reduction and tetracosane with 50.28% reduction. In all sampling time, the initial octadecane level was significantly higher than the final octadecane level in soil with E. fetida (P<0.05). Also, the initial hexadecanoic acid methyl ester level was significantly higher than the level of the hydrocarbon in the soils with E. fetida after 96 hour incubation and soil without the earthworm after 72 hours incubation (P<0.05). After the 24 hours incubation the octadecane level in soil with E. fetida was significantly lower than the initial level and the level in soil without the earthworm (P<0.01).The results showed that E. fetida enhances the degradation and reduction of TPH levels in soils and therefore can be used for cleaning up of soils contaminated with mixture of petroleum products. This is useful in reclaiming mechanic workshop soils for agricultural purposes hence increase in food production. Keywords: Vermiremediation, petroleum, contamination, earthworm, Eisenia fetida